Relationship between postoperative nodal skip metastasis of mid-thoracic esophageal squamous cell carcinoma and patient prognosis and its value in guiding postoperative adjuvant treatment - Gao, Hong-Mei; Zhao, Xiao-Han; Shen, Wen-Bin; Li, You-Mei; Li, Shu-Guang; Zhu, Shu-Chai (Frontiers in Surgery, 2023)
Objective To evaluate the predictive role of nodal skip metastasis (NSM) in the prognosis of lymph node-positive mid-thoracic esophageal squamous cell carcinoma, and to evaluate the significance of postoperative adjuvant treatment in patients with different sites of metastatic nodes. Methods A retrospective analysis was performed on clinical data of 321 lymph node-positive mid-thoracic esophageal squamous cell carcinoma patients who underwent surgery in the Fourth Hospital of Hebei Medical University. Based on the site and condition of lymph node metastasis by postoperative pathology, the patients were divided into two groups: NSM group and non-NSM (NNSM) group. The propensity score matching method was employed to match the two groups. The prognostic factors of patients before and after propensity score matching as well as the effect of different adjuvant treatment modes on the prognosis of patients before and after propensity score matching were analyzed. SPSS 29.0 statistical software was used for analysis. Results: NSM served as the treatment group and NNSM as the control group. Propensity score matching in a 1:1 matching ratio was performed, and 103 patients was assigned to NSM group and NNSM group respectively. Significant differences were found in the 3- and 5-year OS and DFS between the two groups before propensity score matching, as well as in the 3- and 5-year OS of patients after PSM (P<0.05). Multivariate analysis showed that gender, postoperative adjuvant treatment mode, N stage and lymph node metastasis were independent risk factors for OS and DFS in 206 patients after propensity score matching (P<0.05); Postoperative adjuvant chemotherapy and radiotherapy provided significant survival benefit, specifically prolongation of OS and DFS of all patients before propensity score matching as well as that of NSM patients after propensity score matching (P<0.05), but no OS and DFS benefit for patients in NNSM group after propensity score matching (P>0.05). Conclusion: Postoperative NSM is a good prognostic factor for patients with mid-thoracic esophageal squamous cell carcinoma, postoperative adjuvant chemoradiotherapy was recommended for those patients with NSM, thereby gaining survival benefits.